Pengaruh Pengovenan Terhadap Kualitas Organoleptik Telur Asin Yang Dibuat Dengan Cara Basah: The Efect Of Ovenning On Organoleptic Quality Of Wet Method Processed Salted Eggs - Fitri, Yolanda; Lukman, Haris; Resmi, Resmi (Fakultas Peternakan Universitas Jambi, 2021)
This study aims to determine the effect of optimal oven time and the organoleptic quality of salted eggs made using the wet method. The design used in this study was a randomized block design (RBD) with 30 panelists as a group. The treatments given were P0: without oven, P2: oven for 2 hours, P4: oven for 4 hours, P6: oven for 6 hours. The variables observed in this study were color, taste, texture, chewiness, taste, salted egg white and salted egg yolk. The data obtained were analyzed using Kruskal Wallis and X2 analysis. If it turns out to have a real effect, then proceed with the Duncan test. The results showed that the oven had a very significant effect (P <0.01) on the yellow color and the taste of salted egg yolk. As well as a significant effect on the elasticity of salted egg whites (P <0.05). However, it did not significantly affect the taste, aroma, texture of salted egg whites and aroma, texture of elasticity of salted egg yolk. It can be concluded that with an oven time of 6 hours, the best organoleptic quality was obtained from the yellow color, the taste of salted egg yolk and the elasticity of salted egg white. Keywords: Oven Salted Eggs, Oven, Organoleptic, Wet Method